Introduction of Batik Jumputan for The Growth of Creative Thinking in Rural Preschools in Indonesia - Rahayu, Supriati Hardi; Wahyuni, Tri; Imroatun, Imroatun; Niputih, Tuanmakamael (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
This research aims to determine: (1) Implementation of the development of creative thinking through the introduction of jumputan batik in group A PAUD Roudlatul Bunayya in Toyomerto village, Serang Regency (PAUDRB). (2) Supporting and inhibiting factors in the development of creative thinking through the introduction of jumputan batik in group A PAUDRB. This research is a descriptive qualitative type of research. Data collection was obtained using observation, interviews and documentation methods. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The research results show: (1) The implementation of the introduction of jumputan batik was carried out in accordance with the RRPH that was created which contained planning and implementation. The introduction to jumputan batik that was introduced to group A was stamped and jumputan batik. The introduction of Jumputan batik has had a positive impact on children's learning processes and children are given the opportunity and freedom to express themselves so that children can express their thoughts and ideas. (2) supporting factors include: students are enthusiastic about the introduction of jumputan batik, the media is easy to obtain and environmentally friendly, and creative teachers. Meanwhile, the inhibiting factors are children's lack of concentration and lack of self-confidence, inadequate facilities and infrastructure, parents demanding of children. These findings can provide guidance for educational institutions and educators in designing more inclusive and effective learning strategies to facilitate the development of children's creative thinking.